Specification and epigenetic resetting of the pig germline exhibit conservation with the human lineage - Zhu, Qifan (2021)
Primordial germ cells (PGCs) are the founder cells of germline which follow a specific programme of development characterized by a unique transcriptional network and the resetting of epigenome. Studies in human PGCs (hPGCs) are limited to late migratory and gonadal stages as earlier embryos are almost not accessible. Previous study showed that pig PGC (pPGC) share similar developmental programme to human germ cells in vitro. Therefore, pig may serve as an alternative model to provide insight on transcriptional network and epigenetic reprogramming applicable to hPGC. Using single-cell RNA-seq and whole-genome bisulfite-seq with post-bisulfite adaptor tagging (PBAT-seq), here I show that extensive epigenetic reprogramming, including active DNA demethylation, depletion of macroH2A1, global enrichment of H3K27me3 and X chromosome reactivation (XCR), starts in pre- and early migratory pPGC. Concomitantly, there is dampening of glycolytic gene expression and re-expression of some pluripotency genes like those in preimplantation embryos. Evolutionarily young transposable elements (TEs) and gene coding regions resistant to DNA demethylation, i.e. escapees, have also been identified in extremely hypomethylated gonadal pPGCs. Some of those aforementioned events show conservation with hPGCs but not mPGCs, suggesting that the pig is a relevant model for studies on non-rodent PGC specification and transgenerational epigenetic inheritance. Detailed insights into the pig germline will likely contribute to advances in human germline biology, including in vitro gametogenesis